1962
DOI: 10.1128/am.10.3.185-189.1962
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nitric Oxide on Bacteria

Abstract: Nitric oxide, as well as several other oxides of nitrogen, were assayed for their antibacterial action. It is shown that nitric oxide has virtually no effect on bacteria, whereas both NaNO 3 and NaNO 2 appear to have either neutral or stimulatory effects. It is suggested that the formation of nitrous acid is mainly responsible for the quantitative as well as the qualitative changes that occur in the bacterial flora of cured meat. A pH-dependent “nitrite cycle” is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…Data from these studies had shown that the ability of sodium nitrite to kill and to inhibit certain microorganisms was pH dependent, reaching a maximum at the pH range of 4.5-5.5 (24,39). The reactive nitrogen species directly responsible for the toxicity had been proposed to be NO/NOz or HNO2 (24,40). Data from the present study indicate that sodium nitrite effectively killed virulent M. tuberculosis at acidic pH (Table 2).…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…Data from these studies had shown that the ability of sodium nitrite to kill and to inhibit certain microorganisms was pH dependent, reaching a maximum at the pH range of 4.5-5.5 (24,39). The reactive nitrogen species directly responsible for the toxicity had been proposed to be NO/NOz or HNO2 (24,40). Data from the present study indicate that sodium nitrite effectively killed virulent M. tuberculosis at acidic pH (Table 2).…”
Section: Discussionmentioning
confidence: 48%
“…The effector molecules mediating mycobacteriocidal activity that result from acidification of NO2-could be either NO, NO2, or HNOz, or any combination of the three. The antibacterial effect of sodium nitrite, a compound that can form various oxides of nitrogen at acidic pH (12,24), has been known for years (39). The mechanisms for this effect had been studied extensively in the past as a result of the widespread use of NO2-in meat curing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This confirmed a previous report (6) that induction of the MO N02--producing pathway correlates with and is required for cytostasis in this system . Since N02-can be growth inhibitory (13)(14)(15)(16), we tested if exogenous NaN02 could cause cytostasis in the cocultures. NaN03 served as a control.…”
Section: N02 -Synthesis (O) and [ 3 H]mentioning
confidence: 99%